Product leadership how top product managers launch awesome products and build successful teams - Banfield, Richard; Eriksson, Martin; Walkingshaw, Nate (O'Reilly, 2017)
What is product management? -- Why is product leadership so relevant? -- Being a great product leader -- Is there a formula for success? -- Hiring product leadership -- The startup organization -- The emerging organization -- The enterprise organization -- Mapping the partner ecology -- Final words
Includes bibliographical references and index
Keywords: Produktentwicklung; Informationstechnik